2018
DOI: 10.1177/1535370218813525
|View full text |Cite
|
Sign up to set email alerts
|

The profile analysis of circular RNAs in human placenta of preeclampsia

Abstract: A total of 70 pregnant women were recruited for this study, including 35 early onset preeclampsia (PE) and 35 normal pregnant women. By RNA sequencing, the circular RNA (circRNAs) in placenta were identified. Differentially expressed circRNAs were bioinformatics analyzed with gene ontology, Kyoto Encyclopedia of Genes and Genomes, and circRNA–miRNA interaction prediction. Quantitative real time polymerase chain reaction(qRT-PCR) assay was used to verify the results. Compared with the normal pregnant women, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 40 publications
(49 reference statements)
1
28
0
Order By: Relevance
“…However, how these differentially expressed circRNAs affect the function of trophoblasts and thus participate in the development of PE, has not yet been reported. Previously, we identified differentially expressed circRNAs by RNA sequencing and verified their potential functions using qPCR and bioinformatics [12]. In particular, circRNA of pregnancy-associated plasma protein A (circ-PAPPA) (hsa circ 0088227), which originates from the pregnancy-associated plasma protein A (PAPPA) gene, attracted our attention.…”
Section: Introductionmentioning
confidence: 99%
“…However, how these differentially expressed circRNAs affect the function of trophoblasts and thus participate in the development of PE, has not yet been reported. Previously, we identified differentially expressed circRNAs by RNA sequencing and verified their potential functions using qPCR and bioinformatics [12]. In particular, circRNA of pregnancy-associated plasma protein A (circ-PAPPA) (hsa circ 0088227), which originates from the pregnancy-associated plasma protein A (PAPPA) gene, attracted our attention.…”
Section: Introductionmentioning
confidence: 99%
“…In another analysis, Zhou et al () found that 49 circRNAs differently expressed in placental tissues of women with pre‐eclampsia, compared to healthy pregnant women. Two of them were upregulated and others downregulated in pre‐eclampsic cases.…”
Section: Circrnas and Pre‐eclampsia: Latest Evidencementioning
confidence: 99%
“…One of the main functions of circRNAs is the activation of miRNA sponge which is involved in the pathogenesis of several diseases. On the other hand, some studies have suggested that circRNAs might play an important role in the pathogenesis of pre‐eclampsia through activating miRNA sponge method (Jiang et al, ; Qian et al, ; Zhou et al, ). Thus, we hypothesize that alterations in the levels of circRNAs may be involved in the pathogenesis of pre‐eclampsia and associated with its incidence.…”
Section: Circrnas and Pre‐eclampsia: Latest Evidencementioning
confidence: 99%
See 1 more Smart Citation
“…long non-coding RNA, miRNA, circular RNA) in the placenta ( Cox et al , 2015 ). Differential placental expression of non-coding RNAs has been investigated in pre-eclampsia ( Gunel et al , 2017 ; Hu et al , 2018a ; Lykoudi et al , 2018 ; Zhou et al , 2018 ), GDM ( Li et al , 2015 ; Wang et al , 2019b ), IUGR or SGA pregnancies ( Wen et al , 2017 ; Ostling et al , 2019 ) and early pregnancy loss ( Hosseini et al , 2018 ). The use of RNA sequencing technologies to further characterize these non-coding RNAs provides a tantalizing approach to identify and develop new biomarkers and therapeutic targets for pregnancy complications.…”
Section: Knowledge Gaps and Future Directionsmentioning
confidence: 99%